O DIREITO SÓLIDO NA MODERNIDADE LÍQUIDA: a crise de efetividade do direito criminal na contemporaneidade - COELHO, Thales Dyego de Andrade (2017)
The Polish sociologist Zygmunt Bauman defined the present moment of contemporary society as that of liquid modernity, understood as the phase of modernity in which nothing is done to last, an era marked by uncertainty and fluidity in all aspects of social life. In this context, the Law and especially Criminal Law, do not pass unharmed. Thus, the present work starts from the understanding of the phenomena characteristic of liquid modernity, such as the divorce between power and politics, the struggle between the individual and the citizen, as well as the change of ethics in postmodernity, in order to understand what function has actually been occupied by Criminal Law in society and that has led to a state of crisis of effectiveness. Therefore it will be examined the current crisis context of Criminal Law as a whole, including not only Criminal Law and its epistemology, but Criminal Policy itself and Criminology, which is represented by the phenomenon called Criminal Law expansionism and which would have culminated in the discursive legitimization of different criminal treatment of certain individuals, the Criminal Law of the Enemy outlined by Günther Jakobs. It is only from the understanding of the problem from different points of view that a sketch of an effective criminal science can be drawn and that captures in its rationality the different nuances of the social phenomenon that it seeks to regulate, exercising a function of Solid Law that can serve as safe harbor and shield for the citizen facing the difficult context of uncertainties of liquid modernity.